Exploring Dalit Students’ Perceptions towards Learning English - Nepali, Bimal (Journal of Educational Research and Innovation, 2024)
This study explores the perceptions of Dalit students towards learning English, aiming to examine their experiences, challenges, and motivations in educational contexts. This study employed a quantitative survey methodology to explore the perceptions of Dalit students towards learning English. A structured questionnaire was the primary tool for data collection, allowing for systematic and quantifiable measurement of students' attitudes, motivations, experiences, and challenges in learning the language. The target population for this research consists of Dalit students enrolled in selected five community schools of Birendranagar Municipality. The findings reveal that while English is perceived as a language of opportunity and upward mobility, many Dalit students face significant barriers, including limited access to quality instruction, socio-cultural discrimination, and a lack of supportive learning environments. Despite these challenges, participants express a strong desire to learn English, driven by aspirations for better educational and career prospects. The study highlights the need for more inclusive language policies and targeted support for marginalized students, ensuring equitable access to English education. The paper concludes with recommendations for policymakers, educators, and stakeholders to address the existing gaps and promote social justice in English language learning for Dalit students.